A case study of an excellence English teacher and her factors of excellence / Intan Munirah Radzi - Radzi, Intan Munirah (Faculty of Education, 2014)
The study was conducted to see whether the excellent teacher’s habits matches Seven Habits of Highly Effective People by Steven Covey and to see how the teacher matches the characteristics of good language teacher in order to be excellent. An excellent teacher of English subject was selected from a school somewhere in Klang. The respondent was being observed and interviewed. The observation was done within four months. The study revealed that the respondent possessed most of Seven Habits of Highly Effective People and the characteristics of good language teacher. For further research, this study can be improved by increasing the number of respondent, time frame to conduct the observation and the factors that influence the respondent’s excellence.